Human Data Science - DL Oberski (Patterns, 2020)
Most data science is about people, and opinions on the value of human data differ. The author offers a synthesis of overly optimistic and overly pessimistic views of human data science: it should become a science, with errors systematically studied and their effects mitigated—a goal that can only be achieved by bringing together expertise from a range of disciplines.